Perilaku Moral dan Religiusitas Siswa Berlatar Belakang Pendidikan Umum dan Agama - Azizah, Nur (Faculty of Psychology, Universitas Gadjah Mada, 2006)
The aim of this research was to examine the differences of moral behavior and religiousity between student’s public school and students Moslem’s school in Bantul. The subjects were 146 students of 8 levels (76 students of public school and 70 students of Moslem’s school). Data collection of this research are concerning moral behavior scale, religiousity scale I (the ideological, the ritualistic, the experiential, the consequential dimensions), religiousity scale II (the intellectual dimension). The research showed that there was significant difference between student’s moral behavior of the public school and Moslem’s school. The moral behavior of the students in public school was better than the moral behavior of the students in Moslem’s school. The research showed that no diffe¬rences of the religiousity between student’s public school and student’s Moslem’s school. The effect of moral behavior to religiousity was reflected in the value of F = 30,653; p < 0,001. The result also suggested that relationship between moral behavior and the religiousity was significant (r = 0,419; p < 0,001). Keywords: Moral behavior. Religiousity